2012
DOI: 10.1007/s13197-012-0845-2
|View full text |Cite
|
Sign up to set email alerts
|

Moisture content prediction of Iranian wheat using dielectric technique

Abstract: The moisture measurement is the most important criteria in harvesting and post harvesting processing of wheat. This paper investigates the moisture dependent dielectric constant and calibration equation of three most cultivated wheat varieties in Iran. An instrument with a cylindrical capacitive sensor was used to measure the dielectric constant of grain at different moisture contents. Samples were prepared at five levels of moisture content. To validate the proposed equations, the dried material dielectric co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…The studied sample of wheat is within the Mexican Standard for moisture content and density (marked as maximum 13 % and minimum 760 kg/m 3 for moisture content and density, respectively, by NMX-FF-036NMX-FF-036 1996). Additionally, the characteristics of barley, corn, sorghum and wheat are similar to those reported for the same cereals by Nelson and Trabelsi (2011) and for wheat reported by Soltani and Alimardani (2014).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The studied sample of wheat is within the Mexican Standard for moisture content and density (marked as maximum 13 % and minimum 760 kg/m 3 for moisture content and density, respectively, by NMX-FF-036NMX-FF-036 1996). Additionally, the characteristics of barley, corn, sorghum and wheat are similar to those reported for the same cereals by Nelson and Trabelsi (2011) and for wheat reported by Soltani and Alimardani (2014).…”
Section: Resultssupporting
confidence: 80%
“…Soltani and Alimardani (2014) also reported the dielectric properties of Iranian wheat to predict its moisture content. However, dielectric properties relevant to develop microwave heating protocols with disinfestation or decontamination purposes have not been published.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation results in table 2 showed that all three grain samples, phase shift was statistically correlated with grain mass. Dielectric constant (ε') and loss factor (ε") were both correlated with grain mass at fairly low level but correlated with moisture content at high level, which meant both ε' and ε" were valid indicators to reflect moisture variations in the estimation model (Soltani and Alimardani 2014;Trabelsi et al, 2016).…”
Section: Results and Discussion Correlations And Significance Analysi...mentioning
confidence: 99%
“…For estimating the moisture content, reduction in the mass of the films is observed when it is exposed to the 100ºC.The net variation between initial and final moisture content of the film provide statistics about the moisture content, according to the formula used by Soltani et al (2014) …”
Section: Moisture Contentmentioning
confidence: 99%